Efficient synthesis of benzofuranones: N-heterocyclic carbene (NHC)/base-catalyzed hydroacylation-stetter-rearrangement cascade - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
A N-heterocyclic carbene/base-catalyzed cascade reaction leading to the formation of functionalized benzofuranones is reported. The reaction proceeds via an intramolecular hydroacylation of unactivated alkynes followed by an intermolecular Stetter reaction and a base-catalyzed chromanone to benzofuranone rearrangement.